Efeitos citoprotetor e citotóxico de Annona glabra (Annonaceae) - SARMENTO, Rosana Moura (Universidade Federal do Pará, 2017)
The present study evaluated the cytotoxic and cytoprotective potential of ethanolic extract obtained from the shells of Annona glabra, its fractions and isolated substances. The powder obtained from A.glabra husks was subjected to maceration with ethanol for 7 days, and the solution was concentrated in a rotavaporator to residue. The ethanolic extract from A.glabra was partitioned between aqueous hexane: methanol (9: 1). The methanolic fraction was fractionated in chromatographic column using as Sephadex stationary phase and mobile phase the methanol. The cytotoxicity of the ethanolic extract and fractions was evaluated by the MTT cell viability assay ([3- (4,5-dimethylthiazol-2-yl) -2,5-diphenyltetrazolium bromide]). The extract, fractions and subfractions were submitted to thin layer chromatography (CCD) analysis, and pooled according to similar characteristics. The 50% cytotoxic concentration (IC 50) was determined by linear regression. Fractions of the extract with IC50 ≤ 30 μg / mL and isolated substance with IC50 ≤ 4 μg / mL are considered cytotoxic. Fractions with moderate to low cytotoxicity were submitted to the induction of apoptosis and DNA fragmentation by flow cytometry. Also, these samples were submitted to evaluation of oxidative stress by the TEAC and DPPH method. The extract of A. glabra (8.39% yield) was partitioned to give the methanolic fraction (yield 88.14%) and hexane fraction (yield 8.08%). Ethanolic extract, methanolic fraction and rutin showed low cytotoxicity (IC50 = 137.7, 139.4,> 200 μg / mL, respectively). Hexanic fraction and subfractions 17 and 19 showed moderate non-significant cytotoxicity (IC50 = 45.07, 53.45, 80.65 μg / mL, respectively). All the evaluated samples did not induce apoptosis cells, however, ethanolic extract, hexane fraction and rutin promoted changes in the cell morphology. However, hexanic fraction, subfractions 6 and 7 showed the ability to fragment DNA from cells. The fractionation of the ethanolic extract favored the cytotoxic potential, with the hexane fraction being the most promising, and the antioxidant capacity was also favored, with group 5 being the most promising. These results suggest that A. glabra samples have low cytotoxic potential, and the mechanism involved is not related to the induction of apoptosis, and the ethanolic extract contains substances with antioxidant capacity.